2023
DOI: 10.1097/md.0000000000033773
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia caused by Schizophyllum commune in a patient with diabetes: A case report and comprehensive literature review

Abstract: Rationale: Schizophyllum commune (S. commune) is a basidiomycete bracket fungus that rarely causes invasive fungal infections. It is often misdiagnosed as other invasive fungal disease because of its atypical clinical features. Here we report a case of pneumonia due to S commune and review the relevant literature. Patient concerns and diagnoses: A 55-year-old male with a history of diabetes and poor glycemic control presented with cough and sputum for half a month. Laboratory examination showed elevated peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In European and American countries, it is considered inedible, largely due to cultural tastes, small stature, and its presumed leathery texture. Literature reports on S. commune have mainly implicated the fungus with multiple pulmonary manifestations ranging from sinusitis, allergic bronchopulmonary mycoses, asthma, chronic eosinophilic pneumonia, and so on [ 251 , 252 ].…”
Section: Resultsmentioning
confidence: 99%
“…In European and American countries, it is considered inedible, largely due to cultural tastes, small stature, and its presumed leathery texture. Literature reports on S. commune have mainly implicated the fungus with multiple pulmonary manifestations ranging from sinusitis, allergic bronchopulmonary mycoses, asthma, chronic eosinophilic pneumonia, and so on [ 251 , 252 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data on antifungal susceptibility testing methods and cut off values for breakpoints are not available for S.commune specifically. 11 In a study, it was found that there were five tested clinical isolates of S.commune that were found to be susceptible to itraconazole, voriconazole and amphotericin B. 12 Based on the previous case study of S. commune causing ulceration of the hard and soft palate, Amphotericin B is the therapy that looks promising.…”
Section: Discussionmentioning
confidence: 99%